Turtles in trouble. Conservation ecology and priorities for Australian freshwater turtles - Petrov, Kristen; Sutcliffe, Sarah; Truscott, Helen; Kutay, Cat; Eisemberg, Carla C.; Spencer, Ricky J.; Lawler, Ivan; Bower, Deborah S.; Van Dyke, James U.; Georges, Arthur (Austral ecology, 2023)
The Australian freshwater turtle fauna is dominated by species in the family Chelidae. The extant fauna comprises a series of distinct lineages, each of considerable antiquity, relicts of a more extensive and perhaps diverse fauna that existed when wetter climes prevailed. Several phylogenetically distinctive species are restricted to single, often small, drainage basins, which presents challenges for their conservation. Specific threats include water resource development, which alters the magnitude, frequency, and timing of flows and converts lentic to lotic habitat via dams and weirs, fragmentation of habitat, sedimentation, nutrification, and a reduction in the frequency and extent of floodplain flooding. Drainage of wetlands and altered land use are of particular concern for some species that are now very restricted in range and critically endangered. The introduced European red fox is a devastatingly efficient predator of turtle nests and can have a major impact on recruitment. In the north, species such as the northern snake‐necked turtle are heavily depredated by feral pigs. Other invasive animals and aquatic weeds dramatically alter freshwater habitats, with consequential impacts on freshwater turtles. Novel pathogens such as viruses have brought at least one species to the brink of extinction. Species that routinely migrate across land are impacted by structural simplification of habitat, reduction in availability of terrestrial refugia, fencing (including conservation fencing), and in some areas, by high levels of road mortality. We report on the listing process and challenges for listing freshwater turtles under the Australian Environment Protection and Biodiversity Conservation Act, summarize the state of knowledge relevant to listing decisions, identify the key threatening processes impacting turtles, and identify key knowledge gaps that impede the setting of priorities. We also focus on how to best incorporate First Nations Knowledge into decisions on listing and discuss opportunities to engage Indigenous communities in on‐ground work to achieve conservation outcomes. The freshwater turtle fauna in Australia, mainly consisting of species in the family Chelidae, is characterized by distinct lineages that have survived from a more diverse past. Conservation efforts face challenges due to habitat fragmentation, water resource development, invasive predators like foxes and feral pigs, altered land use, and the impact of invasive species and pathogens. This article discusses the process of listing turtles under the Australian Environment Protection and Biodiversity Conservation Act, highlights key threats and knowledge gaps, and explores the inclusion of First Nations Knowledge and the engagement of Indigenous communities in conservation initiatives.